2006
DOI: 10.2337/db05-1188
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenols Stimulate AMP-Activated Protein Kinase, Lower Lipids, and Inhibit Accelerated Atherosclerosis in Diabetic LDL Receptor–Deficient Mice

Abstract: Because polyphenols may have beneficial effects on dyslipidemia, which accelerates atherosclerosis in diabetes, we examined the effect of polyphenols on hepatocellular AMPactivated protein kinase (AMPK) activity and lipid levels, as well as hyperlipidemia and atherogenesis in type 1 diabetic LDL receptor-deficient mice (DMLDLR ؊/؊ ). In HepG2 hepatocytes, polyphenols, including resveratrol (a major polyphenol in red wine), apigenin, and S17834 (a synthetic polyphenol), increased phosphorylation of AMPK and its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

32
484
2
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 597 publications
(528 citation statements)
references
References 50 publications
32
484
2
5
Order By: Relevance
“…Results of this study showed that the leaves extract of Sauropus androgynus at level of 9 g/kg diet could reduce the fat content of meat in broiler chickens fed a Effect Sauropus androgynus on Fat Disposition in Broiler (U. Santoso et al) 179 Compounds that play a role in lowering fat contents might be alkaloid and non alkaloid (Santoso et al, 2010b) (Yu et al, 2006), flavonoid (Zarrouki et al, 2010), tannin (Aiura and de Carvalho, 2007), polyphenol (Zang et al, 2006). SALE supplementation up to 9 g/kg diet could lower cholesterol contents of meat to normal contents (control).…”
Section: Levels Of Fat Protein and Cholesterol Meatmentioning
confidence: 98%
See 1 more Smart Citation
“…Results of this study showed that the leaves extract of Sauropus androgynus at level of 9 g/kg diet could reduce the fat content of meat in broiler chickens fed a Effect Sauropus androgynus on Fat Disposition in Broiler (U. Santoso et al) 179 Compounds that play a role in lowering fat contents might be alkaloid and non alkaloid (Santoso et al, 2010b) (Yu et al, 2006), flavonoid (Zarrouki et al, 2010), tannin (Aiura and de Carvalho, 2007), polyphenol (Zang et al, 2006). SALE supplementation up to 9 g/kg diet could lower cholesterol contents of meat to normal contents (control).…”
Section: Levels Of Fat Protein and Cholesterol Meatmentioning
confidence: 98%
“…This means SALE supplementation alone was not enough to lower cholesterol content to below control. Compounds that play a role in lowering cholesterol might be alkaloids and non-alkaloids (Santoso et al, 2010), saponins (Son et al, 2007), polyphenol (Ngamukote et al, 2011;Zang et al, 2006), flavonoid (Shrime et al, 2011). Patil et al (2010) reported that the reduction of cholesterol and triglycerides by alkaloids were in part caused by the reduction of lipogenic enzymes activities and increased bile acid excretion in feces.…”
Section: Levels Of Fat Protein and Cholesterol Meatmentioning
confidence: 99%
“…Furthermore, the molecular mechanisms through which Scutellaria baicalensis acts are unknown. Recently, beneficial effects on obesity, diabetes and fatty liver have been reported for various flavonoids, which are thought to act through AMPK [9][10][11] . Therefore, the bioactive flavonoids such as baicalin in Scutellaria baicalensis are of particular interest.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, polyphenols have been reported to reduce hyperlipidemia and hyperglycemia, and their effects on lipogenesis have been suggested to be mediated via activation of the AMP-activated protein kinase (AMPK) [9][10][11] . In this relation, AMPK has emerged as an important regulator of lipid metabolism at the cellular and systemic levels, and dysfunction of hepatic AMPK represents a key mechanism for hepatic lipid accumulation and hyperlipidemia with hepatic steatosis in genetically obese rodents [12,13] and in high-fat-fed mice [13] and rats [9,14] .…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest that the prevention of LDL oxidation and suppression of OX-LDL-induced cellular effects can have a beneficial effect upon the progression of endothelial injury. The pathophysiological effects of OX-LDL on vascular cells have been well documented; recently, studies have reported that various components in foods can attenuate lipid oxidation [22][23][24][25] . Dietary isoflavones have been suggested to be protective against a range of diseases, including cardiovascular diseases, osteoporosis, and cancer, and have also been reported to alleviate menopausal symptoms in postmenopausal women [26][27][28] .…”
Section: Discussionmentioning
confidence: 99%